THE HISTORY OF THE SOCIAL AND CULTURAL LIFE OF THE TAJIKS OF THE NURATA OASIS (World Bulletin of Social Sciences, 2021)
Since ancient times, the territory of Uzbekistan has been inhabited by numerous nationalities who lived in peace and harmony, carried on a common household economy. The article describes the life of the Tajiks of the Nurata oasis, their traditions, cultural customs, economic life. Reforms of the state aimed at the socio-economic support of various nationalities, including ethnic Tajiks, through the creation of institutional institutions, the development of social infrastructures are highlighted
Keywords: Nations; nationalities; Tajiks; Nurata